The effect of the Morningstar rating on fund flows in the Norwegian mutual fund market - Aasheim, Linn Kristin (2013)
This thesis analyzes the effect of Morning rating changes in equity funds available for sale in Norway. A study carried out in USA (Del Guercio & Tkac, 2008), reported that the Morningstar rating has significant independent influence amongst retail investors, resulting in abnormal inflows to top-rated funds. The findings are important because the large abnormal flows associated with top Morningstar ratings cause incentives for portfolio managers to chase higher ratings in order to attract fund flows. Contrary to findings from the US market, the results in this study indicate only weak evidence that the Morningstar rating has influence in the Norwegian market. The study goes on to investigate whether Norwegian retail investors should take the Morningstar rating into account in the investment decision to achieve higher future returns. The method partially follows Blake & Morey (2000) to investigate if the Morningstar rating is a predictor of mutual fund performance for funds in the Norwegian market. The results exhibit that average ratings decrease over time for top-rated funds and increase for lower-rated funds. The absence of performance persistence is consistent with the patterns that can be observed in the overall mutual fund industry. The lack of predictive power in Morningstar ratings can rationalize why Norwegian retail investors neglect to move flows to the top-rated funds.